In the web of class delinquents and reformers in Boston, 1810s - 1930s - Schneider, Eric C. 1951-2017 (New York Univ. Press, 1992)
The creation of the juvenile court during the Progressive Era unified the juvenile justice system under the auspices of the state. But this achievement has been vastly overrated. Delinquents and their families participated actively in reform from the founding of the first reformatories through the establishment of the juvenile court, and constantly forced reformers to rethink and reshape their programs. Eric C. Schneider argues that programs to prevent delinquency and to reform delinquents must be understood as part of the history of social welfare. Reform in social welfare meant limiting relief costs while supplying the poor with the cultural values reformers saw as the only real insurance against poverty. Cultural reform led inevitably to work with children, who seemed easier to mold than adults. But the cultural reform tradition failed, because children turned out to be less malleable than reformers thought, and cultural reform itself was an inadequate solution to delinquency and poverty. And while reformers understood the difficulties of handling adolescents, they rarely questioned their assumption that by reforming the individual they could reshape society. Today the cultural reform tradition remains paradigmatic, making this study both timely and vital.
Keywords: Geschichte 1810-1940; Geschichte 1810-1930; Enfants - Protection, assistance, etc - Massachusetts - Boston - Histoire; Enfants pauvres - Massachusetts - Boston - Conditions sociales; Hervormingen; Jeugdcriminaliteit; Service social aux jeunes délinquants - Massachusetts - Boston - Histoire; Services correctionnels pour mineurs - Massachusetts - Boston - Histoire; Geschichte; Child welfare -- Massachusetts -- Boston -- History; Juvenile corrections -- Massachusetts -- Boston -- History; Poor children -- Massachusetts -- Boston -- Social conditions; Social work with juvenile delinquents -- Massachusetts -- Boston -- History; Jugendhilfe; Jugendlicher Täter; Sozialarbeit; Jugendstrafvollzug; Boston, Mass.